The party lists and their electoral performance the case of partido ng manggagawa (PM) in Barangay Bolilao, Mandurriao and Anakpawis Party (AP) in Barangay Punong, Lapuz during the 2004 elections. - Gadnanan, May Corona
The study is conducted in order to determine the electoral performance of Partido ng Mangagawa (PM) in Barangay Bolilao, Mandurriao and the Anakpawis Party (AP) in Barangay Punong, Lapuz. The objectives of the study are: (1) to identify the campaign strategies and party structure of the two Party lists in 2004 election: (2) to determine the voting pattern of the voters and; (3) to examine the motivation behind these votes, such as why do they vote or not vote for the Party., This is a descriptive analytical study, which employed survey research methods and key informant interviews for the primary data. The findings of the study revealed that the major campaign strategies employed by both parties are giving of campaign literature and printed materials like posters,,leaflets and sample ballots of caucuses or meetings, house-house campaigns and media advertisements or exposure. In terms of the party structure, both are extensive in nature. As to the direction of votes, there is a difference between the major reasons of voting the Party. For the respondents of Punong most of them voted AP Party for its party's position on certain issues which they also believed. While majority of the Bolilao respondents voted the PM Party because they were members of the party and its allied organizations. On the other hand, those who did not vote for the said parties were because they failed to vote for the party list slot due to lack of understanding of and confidence on party lists. The data generated also revealed the significant role played by the allied urban poor organizations in both the two barangays that helped the parties in the election. With regards to party structure, data supported the idea of Blondel, saying that the more extensive the party, the more likely they are centralized. the findings also affirmed the study of Jewell and More house that the presence of affiliated associations such as both of the Parties' allied group is also important to the party's success. The results on campaign strategies on the other hand, supported the studies of Goldenberg and Traugott that the best technique for a highly targeted appeal is the use of campaign handouts. Moreover, the utilization of media in campaign supports the study of Lazarsfeld that the more people read and heard about the campaign in the mass media, the more likely they know about the candidates stands on the issues. The direction of votes of the respondents in Bolilao supports Giddings and his Columbia University students' study that the people's social or group membership largely determines an individual;s political action. While that of Alford study wherein voters tend to vote a party for the reason that their class interests are being represented by the party was found to be true in the case of the respondents in Punong, Lapuz. Subsequent to the findings of this study, the researcher presented policy recommendations like further education campaigns to the electorate to let them understand the importance of the Party lists; the expansion of their membership base; the strengthening of their alliance with the urban poor organizations; and further visibility of the party in the barangay. Further studies must also be made especially on the areas of social class position of voters affecting their votes, electoral law's role in the party list, the hindrances encountered by the parties during elections, the contributions or achievements made by the Party lists and a comparison on how PM and AP's different ideologies affected their campaigns.